Responsive and resilient supply chain network design under operational and disruption risks with delivery lead-time sensitive customers. (May 2017) - Fattahi, Mohammad; Govindan, Kannan; Keyvanshokooh, Esmaeil
Abstract: We address a multi-period supply chain (SC) network design where demands of customers depend on facilities serving them based on their delivery lead-times. Potential customer demands are stochastic, and facilities' capacity varies randomly because of possible disruptions. Accordingly, we develop a multi-stage stochastic program, and model disruptions' effect on facilities' capacity. The SC responsiveness risk is limited and, to obtain a resilient network, both mitigation and contingency strategies are exploited. Computational results on a real-life case study and randomly generated problem instances demonstrate the model's applicability, risk-measurement policies' performance, and the influence of mitigation and contingency strategies on SC's resiliency.